How cancer patients get fake cancer information: From TV to YouTube, a qualitative study focusing on fenbendazole scandle - Kim, Jee Hyun; Oh, Kyoung Hee; Shin, Hye Young; Jun, Jae Kwan (Frontiers in Oncology, 2022)
Background: Korean society has faced challenges in communicating with cancer patients about false information related to complementary alternative medicine. As the situation has become severe with the 2020 fenbendazole scandal, the demand for reliable information from health authorities has increased. Objectives: This study aimed to examine patients’ acquisition patterns and perception of false information by presenting empirical evidence to help health authorities enable effective preemptive responses in the cancer communication context. Method: We conducted a focus group interview with 21 lung cancer patients who were informed about fenbendazole based on a semi-structured questionnaire with three categories: 1) acquisition channel of the general cancer information and the false information, 2) quality of obtained information, and 3) perception toward it. The interviewees, comprising 13 men and eight women, were aged 50 or older. Participants' current stages of cancer were stages one, three, and four and there were seven people in each stage. Results: 1) Acquisition channel: Participants had their first encounter with false information through the TV, while the channels to obtain general cancer information were through Internet communities or portal sites. YouTube was a second channel to actively search for information regardless of the information type. 2) Information quality: participants had only fragmented information through media. 3) Perception: Most patients had a negative attitude toward complementary and alternative medicine information such as fenbendazole. They perceive that it needs to be verified by experts and filtered according to their arbitrary criteria. They had vague expectations based on a hope for "what if” at the same time. Conclusions: Despite the complex media environment, traditional or legacy media is an important channel to encounter information. YouTube is independent of other media as an "active" information-seeking channel. Patients required the appropriate intervention of experts and governments because they perceived that they had obtained irrational and unreliable information from the media. Suggestions are made about how health authorities can construct an effective communication system focusing on the user to prevent patients from getting false cancer information